Predictors of prosecutorial decisions in reports of child sexual abuse - Block, Stephanie D. (Child maltreatment, 2023)
A retrospective examination of 500 child sexual abuse reports to prosecutor’s offices analyzed case progress and predictors of attrition, including details about alleged perpetrator(s), victim(s), their families, and other case characteristics. Less than one in five cases proceeded to prosecution. For the full sample, we describe all outcomes and differentiate prosecutors’ decisions to (a) intake/close, (b) investigate/close, or (c) prosecute; these stages comprise a 3-level dependent variable. Because it is important to understand which variables are associated with progress to each stage, we examined unique predictors of the decision to "investigate," and to "prosecute." Our multivariate analyses examine 325 cases with a perpetrator aged 16 and older. Caregiver support and perpetrator age were significant predictors across all outcome variables, while other factors were barriers to the "prosecute" decision only. Results highlight the complexities of case characteristics that are important at different stages of prosecutorial decision-making and inform future interventions.